Nusyuz and its implications in marital relations - Khamsiah Bt Mamat (Kolej Universiti Islam Malaysia, 2022)
Nusyuz or betrayal is a hatred and forbidden thing in Islam. However lately, this problem has been a great issue in our society. Although a lot of ways have been taken by the authorities to handle it. but there are still people who are ignorant about it's bad implications. Because of this. the writer decided to title this paper with the title ' nusyuz. and Its implication in Marital Relations'. Through this writings. the meaning of nusyuz. the causes of nusyuz, its characteristics and also its implication in marital relation are discussed in detail. The method used in writing this project paper is by observations. reading and data collection. The outcome of this writhing shows that nusyuz gives a great implication to the Islamic marital relations. This would then give opportunities to each person to act positively and take effort to solve this problem from being spread widely. Besides, the writer hopes that this writing would give a lot of benefit and lesson to all of us and especially to the wives.